Analisis Kesulitan Siswa SMP dalam Menyelesaikan Soal Kemampuan Berpikir Kritis Matematis - Anita, Anita; Hakim, Dori Lukman (PHI: Jurnal Pendidikan Matematika, 2022)
Critical thinking ability is an ability that needs to be trained in students. The purpose of this study is to analyze the difficulties of junior high school students in solving mathematical critical thinking skills. The method used is descriptive with a qualitative approach. The subjects in this study were students of class VIII at SMPN 1 Pebayuran as many as 32 students. Data collection techniques are obtained by giving questions that have been adjusted to indicators of mathematical critical thinking skills. The instrument used is in the form of a description of six questions, namely indicators of focus, reason, inference, situation, clarity, and overview. The data analysis technique in this study is to analyze the answers of three subjects in terms of six indicators of mathematical critical thinking ability. The results of this study indicate that students have not been able to meet the maximum six indicators of mathematical critical thinking ability. There are still many difficulties for junior high school students in solving mathematical critical thinking skills, namely students find it difficult to find the formula to be used, and have difficulty in the calculation process so that students have difficulty in determining the right conclusions or reasons, besides students have difficulty understanding the questions given so that in determining the solution to answer the question becomes less precise.